Hygienic Assessment of Working Conditions According to the Severity and Intensity of the Labor Process in Poultry Farms (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The division of labor of workers in poultry farms is carried out in accordance with technological processes. According to the research staff, poultry farm workers are distributed as follows: poultry farm operators. — 18.1%, incubator operators - 8.8%, butchers - 24.9%, pickers - 9.1%, sorters-packers - 10.1%. The poultry operator spends 33-34% of his working time distributing feed, while accumulating up to 2896 ± 186 kg / m, which corresponds to average physical activity in accordance with the "Hygienic classification of indicators of labor severity and intensity of working conditions, harmfulness and danger in the production environment" San P and N 0141-03.